IMAGINATION: A KEY TO RELIGIOUS EDUCATION METHODOLOGY - Lucia C. Natividad, Maria (Asian Horizons, 2018)
This paper presents integration as the method to address the common problems in teaching the faith. Integration, proposed by the National Catechetical Directory for the Philippines 2007, is an approach to faith that relates how faith is communicated and the way faith is actually lived in the daily life of the ordinary faithful. As a human capacity, imagination is a way of thinking about faith and how to practice the faith by paying close attention to the divine presence in human experiences and the sources of the faith. It is a key in the process of integrating Christian faith and life that hopefully leads to the maturing of faith. Imagination is a human capacity that sees created reality as a ‘sacrament,’ that is, a revelation of the divine presence creating and sustaining the world and finds appropriate ways to respond to the divine disclosure in the actual living out of the Christian faith of thinking, doing and hoping.